Ahli Waris Pengganti Di Indonesia Dengan Historisitasnya - Muhamad Sauki Alhabsyi; Syahrul Mubarak Subeitan (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2021)
The case of inherition is one of the areas specifically regulated in Islamic law, both the determination of who is entitled (dzawil furudh, ashabah, and dzawil arham) and the details of the number of divisions in the Qur'an. However, with the times came problems and issues of